The Innovation of Internet Industries Transformed to Fourth 4th Industrial Revolution: Threats and Challenges of the Cyber-Enabled Industries - Hilal ALHajri, Haitham (International Journal of Engineering and Technology, 2019)
Artificial intelligence and machine learning to the advanced automation robotics and autonomous portable smart vehicles (cars & drones), along with genetic advances and biotechnology developments. Technological advancement made possible with the aid of Quantum Supercomputing mobile devices, which archived with extended smart digital ledgers (Blockchain Technology) over the backbone of ultra-fast communication technology (5G). This is not seen from the future; instead, it is the works of the contemporary era of indusial revolution 4.0, and we are at the very beginning of this technological era. However, with such rapid development and advancements, a threat is looming from the darkest technological corner, have made its debut, in the form of persistent cyber threat, which is hunting for preys, across all technological platforms, leveraging any possible technological loophole or misconfiguration to their advantage. Cyber and technological criminals will waste no time, in penetration and breaching any technology that comes across their path, and they have always proven to be superior, where the security experts try to fill the gap as they go. This paper will illustrate some of the threats and challenges associated with the development of industry 4.0.